Attenuation of the Model Error in Observer-Based State-Feedback Regulators - Keviczky, L.; Bányász, Cs. (Acta Technica Jaurinensis, 2014)
An equivalent transfer function representation (TFR) is introduced to study the state-feedback/observer (SFO) topologies of control systems. This approach is used to explain why an observer can radically reduce even large model errors. Then the same principle is combined with Youla-parametrization (YP) introducing a new class of regulators.